2009
DOI: 10.1007/s11999-008-0672-y
|View full text |Cite
|
Sign up to set email alerts
|

Cemented versus Uncemented Hemiarthroplasty for Displaced Femoral Neck Fractures

Abstract: Hemiarthroplasty is the most commonly used treatment for displaced femoral neck fractures in the elderly. There is limited evidence in the literature of improved functional outcome with cemented implants, although serious cement-related complications have been reported. We performed a randomized, controlled trial in patients 70 years and older comparing a cemented implant (112 hips) with an uncemented, hydroxyapatite-coated implant (108 hips), both with a bipolar head. The mean Harris hip score showed equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
199
3
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 216 publications
(224 citation statements)
references
References 34 publications
15
199
3
7
Order By: Relevance
“…When we evaluated results of this trial at 1 year, we found comparable outcomes between the two groups for all outcome measures studied [5], and, specifically, the mean Harris hip score was equivalent between the groups at 3 months and 1 year; the duration of surgery and intraoperative blood loss were less in the uncemented group (Table 1). Because few studies have followed randomized hip fracture cohorts up to 5 years, there are limited data on late complications and implant longevity.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…When we evaluated results of this trial at 1 year, we found comparable outcomes between the two groups for all outcome measures studied [5], and, specifically, the mean Harris hip score was equivalent between the groups at 3 months and 1 year; the duration of surgery and intraoperative blood loss were less in the uncemented group (Table 1). Because few studies have followed randomized hip fracture cohorts up to 5 years, there are limited data on late complications and implant longevity.…”
Section: Introductionmentioning
confidence: 81%
“…This prospective, randomized equivalence trial was performed at two hospitals; results previously were reported at 1 year [5]. One hundred fifty fractures were included at a district hospital and 80 fractures were included at a university hospital from September 2004 to August 2006.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations